2021
DOI: 10.1155/2021/5975893
|View full text |Cite
|
Sign up to set email alerts
|

TEX10 Promotes the Tumorigenesis and Radiotherapy Resistance of Urinary Bladder Carcinoma by Stabilizing XRCC6

Abstract: Urinary bladder carcinoma refers to the commonest carcinoma with weak prognostic result for the patient as impacted by the limited treatment possibilities and challenging diagnosing process. Nevertheless, the molecular underpinning of bladder carcinoma malignant progression is still not clear. As a novel core part of pluripotency circuitry, testicular expression 10 (TEX10) plays an actively noticeable effect on reprogramming, early embryo development, and embryonic stem cell self-renewal. Nevertheless, TEX10 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(52 reference statements)
1
8
0
Order By: Relevance
“…These results suggest a crucial role of Tex10 in HCC aggressiveness. Consistent with our results, a previous study showed that Tex10 promotes cell proliferation by stabilizing XRCC6 in urinary bladder carcinoma 7 . Furthermore, Tex10 was also reported to promote colorectal cancer cell proliferation by activating NF‐κB 6 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results suggest a crucial role of Tex10 in HCC aggressiveness. Consistent with our results, a previous study showed that Tex10 promotes cell proliferation by stabilizing XRCC6 in urinary bladder carcinoma 7 . Furthermore, Tex10 was also reported to promote colorectal cancer cell proliferation by activating NF‐κB 6 …”
Section: Discussionsupporting
confidence: 92%
“…Testis expressed 10 (Tex10), a core component of the pluripotency network, plays a critical role in embryonic stem cell self‐renewal and pluripotency and is enriched in association with super‐enhancers in a Sox2‐dependent manner 4 . Furthermore, several studies have identified Tex10 as a putative oncogene that is highly expressed in HCC, esophageal squamous cell carcinoma, colorectal cancer, and urinary bladder carcinoma 5–7 . In our previous study, Tex10 was shown to activate signal transducer and activator of transcription 3 (STAT3) signaling and subsequently promote cancer stem cell properties in HCC 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have shown that Tex10 plays a decisive oncogenic role in HCC tumorigenesis by activating the STAT3 signaling pathway and promoting chemoresistance to maintain cancer stem cell properties. Therefore, targeting Tex10 may provide a novel and effective therapeutic strategy to inhibit the tumorigenicity of advanced HCC [38, 39, 40]. The above results suggest that DF-CAGE helps find cancer druggable genes beyond the known driver genes, which have received relatively little attention in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…We further showed that GAGE, specifically the GAGE12 variant, augmented chromatin dynamics in cancer cells allowing for increased accessibility of DNA damage repair factors, which, upon induction of DNA damage, promoted more efficient DNA repair, protecting cells from DNA-damage-induced apoptosis [ 73 ]. Another study also demonstrated that TEX10 (testis expressed 10) promoted radioresistance in urinary bladder carcinoma by stabilising XRCC6 (x-ray repair cross complementing 6), a key factor required for efficient NHEJ upon induction of DNA damage by agents such as ionising radiation [ 111 ].…”
Section: Cta Biology In Carcinogenesismentioning
confidence: 99%